Telecommunicator Cardiopulmonary Resuscitation: A Policy Statement From the American Heart Association. Issue 12 (24th March 2020) - Kurz, Michael Christopher; Bobrow, Bentley J.; Buckingham, Julie; Cabanas, Jose G.; Eisenberg, Mickey; Fromm, Peter; Panczyk, Micah J.; Rea, Tom; Seaman, Kevin; Vaillancourt, Christian
Abstract : Every year in the United States, >350 000 people have sudden cardiac arrest outside of a hospital environment. Sudden cardiac arrest is the unexpected loss of heart function, breathing, and consciousness and is commonly the result of an electric disturbance in the heart. Unfortunately, only ≈1 in 10 victims survives this dramatic event. Early access to 9-1-1 and early cardiopulmonary resuscitation (CPR) are the first 2 links in the chain of survival for out-of-hospital cardiac arrest. Although 9-1-1 is frequently accessed, in the majority of cases, individuals with out-of-hospital cardiac arrest do not receive lay rescuer CPR and wait for the arrival of professional emergency rescuers. Telecommunicators are the true first responders and a critical link in the cardiac arrest chain of survival. In partnership with the 9-1-1 caller, telecommunicators have the first opportunity to identify a patient in cardiac arrest and provide initial care by delivering CPR instructions while quickly dispatching emergency medical services. The telecommunicator and the caller form a unique team in which the expertise of the telecommunicator is provided just in time to a willing caller, transforming the caller into a lay rescuer delivering CPR. The telecommunicator CPR (T-CPR) process, also previously described as dispatch CPR, dispatch-assisted CPR, or telephone CPR, represents an important opportunity to improve survival from sudden cardiac arrest. Conversely, failure to provide T-CPR in this manner results in preventable harm. This statement describes the public health impact of out-of-hospital cardiac arrest, provides guidance and resources to construct and maintain a T-CPR program, outlines the minimal acceptable standards for timely and high-quality delivery of T-CPR instructions, and identifies strategies to overcome common implementation barriers to T-CPR.